1996
DOI: 10.1093/jat/20.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Fatal Zopiclone Overdose

Abstract: Two cases of death due to the ingestion of zopiclone are presented. Quantitative determinations of zopiclone yielded 1.4-3.9 mg/L in the blood, 0.81 and 8.7 mg/kg in the liver, and 13.5 and 133 mg in the stomach contents. Drug concentrations were interpreted relative to the case findings, published data, and a limited evaluation of therapeutic concentrations found in two cases of therapeutic zopiclone use. Zopiclone was extracted from buffered blood or digested liver or both with n-butyl chloride and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…With increasing frequency of Z-drug prescriptions and abuse in Europe and North America, benzodiazepine screening tests that employ highly sensitive mass spectrometers are recommended to routinely include Z-drugs. Techniques used in the analysis and detection of Z-drugs in various biological matrices are shown in Table 3 [46][47][48][49][50][51][52].…”
Section: Analysis and Detection Of Z-drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…With increasing frequency of Z-drug prescriptions and abuse in Europe and North America, benzodiazepine screening tests that employ highly sensitive mass spectrometers are recommended to routinely include Z-drugs. Techniques used in the analysis and detection of Z-drugs in various biological matrices are shown in Table 3 [46][47][48][49][50][51][52].…”
Section: Analysis and Detection Of Z-drugsmentioning
confidence: 99%
“…In drug-facilitated crimes, where higher doses may have been administered, maximum recommended time intervals for Zdrug detection is 48 h in blood and 72 h in urine [54]. Therapeutic maximal concentrations (C max ) and those found in fatalities are shown in Table 4 [47,51,53,[55][56][57][58][59][60][61][62].…”
Section: Analysis and Detection Of Z-drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of ZOP cases and the concentrations in blood in cases of drug-related violent crimes in Sweden 2008 to 2013 are shown in Table 3. Fatalities resulting from poisoning with ZOP combined with alcohol or other drugs have also been described [73,[112][113][114][115] and cases of fatal ZOP overdose with ZOP concentrations of 1.4-3.9 mg/L in the blood have been reported [116]. An overdose death after ingesting 90 mg of ZOP suggested that this amount could be a minimum lethal dose (in femoral blood the ZOP concentration was 0.254 mg/L) [114].…”
Section: Occurrence Of Zopiclone In Forensic Casesmentioning
confidence: 99%